Ismail Raji Al-Faruqi's Ecotheology: The Concept of Environmental Sustainability Faith-Based - Adli Dzil Ikram (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This article explains an ecotheological view from Ismail Raji Al-Faruqi in overcoming the problem of environmental damage. This research uses literature or document study methods in qualitative research with interpretive analysis. The data used is primary and secondary. Primary data was taken from the work of Ismail Raji Al-Faruqi. Secondary data comes from literature relevant to Ismail Raji Al-Faruqi. Ecotheology, according to Ismail Raji Al-Faruqi, is First, the environmental crisis according to Ismail Raji Al-Faruqi is an environmental situation where natural ecosystems and the environment on earth are threatened due to negative factors caused by humans, who do not realize that humans and nature are interdependent. Second, the Islamic view of the environment is that the environment is God's work, which was created as a place for humans to live, grow, and develop, as well as carry out their obligations as God's creatures. Third, the concept of faith-based environmental sustainability, according to Ismail Raji Al-Faruqi, is maintaining the state of the natural environment by making belief in God the foundation for treating the environment as God has commanded.